Mouseford academy : a fashionable mystery - Stilton, Thea (New York : Scholastic, 2015)
While the Thea Sisters are on a tropical vacation in the Bahamas they find an old pirate map Could it lead to treasure? That's a question the five mice are eager to answer. They venture onto the sparkling Caribbean Sea to follow the map. Its a dazzling adventure.